2003
DOI: 10.1243/095441103762597719
|View full text |Cite
|
Sign up to set email alerts
|

Cyclic flow characteristics in an idealized asymmetric abdominal aortic aneurysm model

Abstract: The flow characteristics and the corresponding hydrodynamic stability in an idealized asymmetric abdominal aortic aneurysm (AAA) model have been investigated using a laser Doppler anemometer. A rectified sine waveform was used to simulate aortic flow conditions (Re(delta) = 806 and alpha = 12.2). The flow around the distal neck of the AAA model undergoes transition and becomes turbulent for a fraction of time shortly after the commencement of the deceleration phases at every flow cycle while the rest of the fl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
12
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 16 publications
2
12
0
Order By: Relevance
“…The CFA waveform in the presence of an AAA shows high levels of spectral broadening, typical of disturbed or turbulent flow in the deceleration phase of the systolic peak. These changes seem to be consistent with the intermittent turbulent bursts observed in the flow within an AAA model during the deceleration phase of the flow cycle in the study byYip and Yu (2003) shown inFigure 1.15. This suggests that AAA may alter the distal flow pattern.…”
supporting
confidence: 88%
See 4 more Smart Citations
“…The CFA waveform in the presence of an AAA shows high levels of spectral broadening, typical of disturbed or turbulent flow in the deceleration phase of the systolic peak. These changes seem to be consistent with the intermittent turbulent bursts observed in the flow within an AAA model during the deceleration phase of the flow cycle in the study byYip and Yu (2003) shown inFigure 1.15. This suggests that AAA may alter the distal flow pattern.…”
supporting
confidence: 88%
“…Yip and Yu (Yip and Yu 2003) also extended their work to investigate sinusoidal flows within idealised, rigid, asymmetric AAA models. They observed that as flow entered the asymmetric AAA model, recirculating vortices were formed either side of the proximal neck, with the vortex on the bulge side larger than on the straight side.…”
Section: Haemodvnamics Of Aaamentioning
confidence: 99%
See 3 more Smart Citations